2021
DOI: 10.3390/ijerph18126464
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Infant Mortality in Brazil, 2010–2020: A Scoping Review

Abstract: Despite the implementation of social and health policies that positively affected the health of the populations in Brazil, since 2009 the country has experienced a slower decline of infant mortality. After an economic and political crisis, Brazil witnessed increases in infant mortality that raised questions about what are the determinants of infant mortality after the implementation of such policies. We conducted a scoping review to identify and summarize those determinants with searches in three databases: LI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 37 publications
0
16
1
2
Order By: Relevance
“…Several other background factors were not analyzed in the current study. It was previously observed that neonatal mortality rate did not differ significantly by mother's age, income, or employment status; on the other hand, mothers with a high school education or less were associated with a higher rate of neonatal deaths, likely due to a lack of awareness about how and when to seek medical care, particularly in emergency situations [1,40]. Some evidence indicates that advanced maternal age is connected with placental malfunction, which may raise the risk of newborn deaths and stillbirths or exacerbate pre-existing maternal medical conditions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several other background factors were not analyzed in the current study. It was previously observed that neonatal mortality rate did not differ significantly by mother's age, income, or employment status; on the other hand, mothers with a high school education or less were associated with a higher rate of neonatal deaths, likely due to a lack of awareness about how and when to seek medical care, particularly in emergency situations [1,40]. Some evidence indicates that advanced maternal age is connected with placental malfunction, which may raise the risk of newborn deaths and stillbirths or exacerbate pre-existing maternal medical conditions.…”
Section: Discussionmentioning
confidence: 88%
“…Neonatal mortality is a public health issue that affects the world's poorest and middleincome countries the most [1]. Even though significant progress has been made in reducing infant mortality over the last three decades, further efforts are needed to improve survival rates and severe complications [2].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the supply of vaccines in the maternity ward and the referral for the continuity of the vaccination schedule in the UBS may also have provided the study with such association. Some studies found an association between the supply of vaccination and declining neonatal and infant mortality (Saso & Kampmann, 2017;Jensen et al, 2019;Bugelli et al, 2021b;Müller-Nordhorn, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The country achieved a considerable reduction in the NMR, from 25.33/1000 in 1990 to 8.5/1000 live births in 2019, although it has recently shown a significant deceleration [1,2]. The improvement of socioeconomic and health policies, such as the implementation of the Unified Health System (SUS) [3]; the "Family Health Strategy" [4], the "Rede Cegonha" strategy, and the "Bolsa Família Program" [5,6], positively impacted the reduction of mortality rates. Still, the infant and child mortality indicators remain high by international standards, with a concentration of deaths in less developed regions, especially the Northern region of Brazil, which has the highest neonatal mortality rate with 11.02 per 1000 live births [1,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%